Internal training load of rhythmic gymnastics athletes - Antualpa, K.; Schiavon, L.; Arruda, A.; Fernandes, S.; Moreira, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The ability for coaches to monitor training load is essential to optimize the process of training. Internal training load (ITL) has been suggested to be an efficacious method for monitoring athlete`s response to a training dose (Impellizzeri et al., 2004). Indeed, session rating of perceived exertion (sRPE) was proposed as a useful, noninvasive, and valid method for monitoring ITL (Wallace et al., 2009). However, there have been few data about the ITL periodization in Rhythmic gymnastics athletes. The aim of this study was to describe the ITL of gymnastics rhythmic athletes via sRPE during an 8-week training period. Methods: Twenty-seven female rhythmic gymnastics athletes subdivided in two groups (G1: n=18, 10.7±1.0 yrs; G2: n=9, 14.1±2.2 yrs) participated. Athletes completed 4 (G1) or 5 (G2) training sessions per week (~14 and 18 training h/week, respectively). The ITL for each session was calculated using the sRPE (CR-10 scale) which was collected 30 min after each training or competitive session. To determine the ITL, the product of session duration (min) and sRPE score rated by the athletes was used. Data are reported as means ± SD. The assumptions of normality and homoscedasticity were verified. A Mixed Model for repeated measurement was applied. The level of significance was set at 5% (p < 0.05). Results: Higher mean ITL values were verified for G2 compared to G1 (4460±812 AU vs. 2248±682 AU). There was an interaction effect (Week*Group), and higher values were observed for weeks with competitions (weeks 3, 7 and 8 for G2, and 3 and 8 for G1) compared to weeks without competitions. Discussion: The present results suggest that the ITL assessed by means of sRPE method is a useful and sensitivity tool for monitoring training of gymnastics rhythmic athletes. The higher training volume performed by G2 compared to G1 seems to have a key role in elevating the ITL. Indeed, higher ITL values could be expected during weeks with official competitions. These results could be taken into account by coaches when planning and monitoring training.